Stillness and Light : The Silent Eloquence of Shaker Architecture - Plummer, Henry (Book collections on Project MUSE., 2009)
Shaker buildings have long been admired for their simplicity of design and sturdy craftsmanship, with form always following function. Over the years, their distinctive physical characteristics have invited as much study as imitation. Their clean, unadorned lines have been said to reflect core Shaker beliefs such as honesty, integrity, purity, and perfection. In this book, Henry Plummer focuses on the use of natural light in Shaker architecture, noting that Shaker builders manipulated light not only for practical reasons of illumination but also to sculpt a deliberately spiritual, visual presen.